SOSIALISASI, KRITERIA DAN MEKANISME SASARAN PENERIMA BANTUAN LANGSUNG TUNAI DANA DESA DI DUSUN SUNGAI MANCUR KECAMATAN TANAH SEPENGGAL LINTAS KABUPATEN BUNGO - Mulia Jaya; Ediyanto Ediyanto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
The location of the research was carried out in Sungai Mancur Kecamatan Tanah Sepenggal Lintas District, Bungo Regency. The research aims to find out the Socialization, Criteria and Target Mechanisms for the Recipients of Direct Village Fund Cash Assistance (BLT-DD), to analyze the obstacles in socialization, Criteria and Mechanisms of Targeting Recipients of Village Fund Direct Cash Assistance (BLT-DD), knowing the efforts made by the village government against the obstacles faced in the Socialization, Criteria and Mechanisms of Targeting Recipients of Village Cash Direct Assistance (BLT-DD). This study uses a qualitative method. The results showed that the Socialization, Criteria and Target Mechanisms for Recipients of Direct Village Fund Cash Assistance (BLT-DD) for Victims of Non-Natural Disasters in the form of a Corona Virus Disease (Covid-19) Pandemic in Sungai Mancur Hamlet, Tanah Sepenggal Lintas District, Bungo Regency were as follows includes (a) the stages of socialization, (b) the stages of determining the criteria for the recipients of the BLT-DD, (c) the target recipients of the Village Fund Direct Cash Assistance (BLT-DD). -DD) for Victims of Non-Natural Disasters in the form of a Corona Virus Disease (Covid-19) Pandemic in Sungai Mancur Hamlet, Tanah Sepenggal Lintas District, Bungo Regency, namely: a) Less than optimal socialization carried out by the hamlet government, b) Hamlet Government Difficult to Determine Criteria Prospective Recipients, c) There is a Negative Perception of the Community towards the Hamlet Government in Determining the Criteria for Candidates for BLT-DD Recipients and the Efforts made by the Government sub-village government regarding the obstacles faced in the Socialization, Criteria and Mechanism of Targeting Recipients of Direct Village Fund Cash Assistance (BLT-DD) for Non-Natural Disaster Victims in the form of a Corona Virus Disease (Covid-19) Pandemic in Sungai Mancur hamlet, Tanah Sepenggal Lintas Regency, Bungo namely: a) Optimizing the socialization of the BLT-DD program to the community, b) BLT-DD being distributed to people who are really affected by Covid-19 and c) Increasing community participation is an effort made by the hamlet government against negative assumptions about the criteria for prospective recipients BLT-DD